Penerapan Disiplin Kerja Pada Badan Keuangan dan Aset Daerah Kabupetan Gorontalo - Nani, Novita Oktavyani R; Sulila, Ismet; Mozin, Sri Yuliyanti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to find out how the implementation of work discipline in the Regional Financial and Asset Agency of Gorontalo Regency is seen based on the indicators of work discipline proposed by Mangkunegara and Octoren (in Ratnasari et al, 2022: 109), namely: 1) Punctuality in arriving at work, 2) Accurate return home time, 3) Compliance with applicable regulations, 4) Use of work uniforms, 5) Responsibility in carrying out tasks. The research method used in this research is a qualitative approach. Data collection techniques were obtained from observations, interviews and documentation with a total of 7 informants. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The results obtained in this research show that the application of work discipline at the Gorontalo Regency Regional Financial and Asset Agency has been implemented as well as possible, however, there are still some employees who are not fully disciplined.